TEACHING STUDENT’S READING COMPREHENSION USING TWO STAY TWO STRAY TECHNIQUE - Wasilah Sa'adah; Fraditha Pinasty Sanjaya (PROJECT (Professional Journal of English Education), 2018)
Reading comprehension is an important part of the reading process. In learning English, students may face some difficulties in learning reading, even though they are students of Senior High School. Therefore the teacher should teach them by appropriate technique to solve their difficulties. This research was conducted to find out the effectiveness of using two stays two stray technique in teaching student’s reading comprehension. It was conducted by quantitative research design with pre-experimental one group pretest-posttest design involving 32 of tenth-grade students of Senior High School in Cianjur. The instrument used in this research was tested (pretest-posttest) which given before and after treatment. The result of data analysis in this research shows the t score is 25.106, it is higher than t table with a degree of freedom (df) 31 and level of significant (2-tailed) at 5% (0.05) which has the value of 2.039. Because t score > t table  (25.106 > 2.039), then Ha is accepted. In other words, there is the effectiveness of using two stays two stray technique in teaching student’s reading comprehension.